PANDEMIA DE COVID-19: ROL DIDACTIC ȘI PERSPECTIVE TEOLOGICE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Covid-19 Pandemic. Didactic Role and Theological Perspectives.An historical-theological approach of the Covid-19 pandemic. In the last 75 years the world has not faced a threat bigger that din Covid-19 pandemic in 2019-2020. With over 2 milion deaths and many secheles the covid had a  didactic impact for the humanity. Restoring the identity and moral compass,  the priorities of life, the love for family, church and humankind with a  planetarium spirituality approach.